Butterfly Vertebrae: A Systematic Review of the Literature and Analysis. Issue 6 (September 2019) - Katsuura, Yoshihiro; Kim, Han Jo
Study Design: Systematic review (Level 4) Objective: To summarize the demographics, clinical presentations, and conditions associated with butterfly vertebrae. Methods: A systematic search was performed of multiple databases. A total of 279 articles were identified for screening. Case series or case reports of butterfly vertebrae with adequate clinical detail were complied. Results: Eighty-two total articles (109 patients) were selected for final inclusion. Sixty-one percent of patients presented with a single butterfly vertebra, while 39% were multiple. The most common location for butterfly vertebrae was T1. Fifty-six percent of cases were associated with a syndrome, the most common being spondylocostal dysostosis. The presence of multiple butterfly vertebra was strongly associated with a syndrome or additional anomalies ( P < .001). Overall, the most common presenting complaint was low back pain. Seventy percent of patients had associated spinal disease. Other organ systems affected included musculoskeletal (43%), craniofacial (30%), neurologic (27%), cardiovascular (24%), genitourinary (23%), gastrointestinal (22%), laboratory abnormality (16%), and endocrine (9%). Conclusions: This study is the largest collection of butterfly vertebrae cases to date. Butterfly vertebrae are associated with spinal deformity and multiple butterfly vertebrae may indicate a syndromic illness. Low back pain or disc herniation may occur with lumbar butterfly vertebrae however the etiology of this phenomena has not been rigorously explained. Many diseases and syndromes are associated with butterfly vertebrae.